Sorderas postnatales. Sordera infantil progresiva, de desarrollo tardío o adquirida | Postnatal hearing loss. Progressive, late-onset or acquired hearing loss in children - Núñez Batalla, Faustino; Jáudenes Casaubón, Carmen; Sequí Canet, José Miguel; Vivanco Allende, Ana; Zubicaray Ugarteche, José (Revista Española de Discapacidad, 2024)